THE ECONOMIC AND GEOPOLITICAL IMPACTS AND IMPLICATIONS OF CHINA’S BELT AND ROAD INITIATIVES ON THE GLOBAL SOUTH - Ezeanyika, Ezeanyika Samuel; Edoun, Emmanuel Innocents; Opurum, Innocent Okwu; Ibekwe, Emmauel Ogueri (African Journal of Social and Behavioural Sciences, 2024)
This paper examines the impacts and implications of the Belt and Road Initiative (BRI) on the global architecture. The BRI's influence extends both in regional and global contexts, with potential indications of a dependency syndrome arising from concerns about debt traps within the Global South regions. Through the use of the dependency theory as an analytical framework, the paper seeks to elucidate the potential implications and impacts of the BRI. Employing a content analysis approach and drawing data from secondary sources, the paper finds the potential of a significant debt trap and economic dependency, as well as the feasible implementation of a counter-hegemonic strategy as policy implications of the BRI. As a result, the paper emphasizes the importance of recognizing the extensive and evolving nature of the BRI's implications. It also prioritizes the need for caution and thorough assessment of the costs and benefits of BRI projects by countries directly involved, ensuring alignment with national development objectives, sustainable practices, and international development standards.